2023
DOI: 10.1007/s44217-022-00027-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of face-to-face versus online learning on student performance in anatomy: an observational study using a causal inference approach

Abstract: Introduction This study aimed to estimate the causal effect of face-to-face learning on student performance in anatomy, compared to online learning, by analysing examination marks under a causal structure. Methods We specified a causal graph to indicate how the mode of learning affected student performance. We sampled purposively to obtain end-semester examination marks of undergraduate and postgraduate students who learned using face-to-face (pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The majority of students in our current study disagreed with the view that lecture clarifications were better when undertaken online as opposed to physical classroom lessons. This is similar to findings from studies conducted in the Czech Republic 94 and Australia 95 where most students reported that lecture clarifications were better when undertaken in face-to-face learning than online. Another study in India also confirmed this by revealing that most students did not favour online learning alone because they were not satisfied with the clarifications as well as the relevance of the study materials that were given to them.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of students in our current study disagreed with the view that lecture clarifications were better when undertaken online as opposed to physical classroom lessons. This is similar to findings from studies conducted in the Czech Republic 94 and Australia 95 where most students reported that lecture clarifications were better when undertaken in face-to-face learning than online. Another study in India also confirmed this by revealing that most students did not favour online learning alone because they were not satisfied with the clarifications as well as the relevance of the study materials that were given to them.…”
Section: Discussionsupporting
confidence: 87%